Investigation of predictors of interest in a brief mindfulness-based intervention and its effects in patients with psoriasis at a rehabilitation clinic (SkinMind): an observational study and randomised controlled trial - Laura Stadtmüller; Markus Eckardt; Christoph Zick; Joerg Kupfer; Christina Schut (BMJ Open)
Introduction Psoriasis (PS) is a chronic inflammatory skin disease accompanied by reduced quality of life. Mindfulness is the ability to focus on the present moment without evaluation. Findings on the effects of 8-week mindfulness trainings in patients with PS reveal positive effects on the severity of the disease and quality of life. However, it remained unclear what distinguishes patients with PS interested in psychological interventions from those without interest and whether also a shorter, namely 2-week mindfulness-based intervention is beneficial in this patient group. This will be investigated with this study.Methods and analyses Data will be collected at a rehabilitation clinic in Germany. The study is divided into two parts: study 1a is an observational study. Its aim is to investigate whether sociodemographic, skin-related and psychological factors are significant predictors of interest in a brief psychological intervention in 127 patients with PS. Study 1b is a randomised controlled trial, in which 60 patients (retrieved from study 1a) will be randomised to an intervention or control group (treatment as usual). The main outcome variables are mindfulness and self-compassion. In addition, mediation analyses will be used in an explorative manner to test whether there is a relationship between mindfulness/self-compassion and the severity of PS and whether it is mediated by itch catastrophising and fear of negative evaluation (first model) or perceived stress (second model).Ethics and dissemination The study protocol has been approved by the University of Giessen. Study results will be disseminated by publication of the results at (inter) national conferences and in scientific journals.Trial registration numbers DRKS00017426 and DRKS00017429.